2021
DOI: 10.1080/21681805.2021.1921024
|View full text |Cite
|
Sign up to set email alerts
|

Prostate biopsy quality and patient experience with the novel Forsvall biopsy needle – a randomized controlled non-inferiority trial

Abstract: Background: Transrectal prostate biopsy (TRbx) carries an increasing risk of infection. The Forsvall Needle Prototype (FNP) is a novel biopsy needle that reduces bacterial load brought across the rectum and may therefore reduce infection risk. The objective of this study was to compare biopsy length, quality and patient experience for the FNP Version 2 (FNP2) versus a standard Tru-Cut needle. Methods: We conducted a randomized, parallel-group, non-inferiority trial with twenty consecutive patients eligible for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In conclusion, we have shown that a smooth, forcedclosed needle design significantly reduces bacterial transfer across the rectal wall in TRbx and is therefore likely to reduce the risk of infectious complications in TRbx. A clinical trial evaluating the quality of prostate specimens obtained by the Forsvall needle has been completed [15] and its ability to reduce infectious complications will be studied further in a prospective, randomized multicentre trial.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, we have shown that a smooth, forcedclosed needle design significantly reduces bacterial transfer across the rectal wall in TRbx and is therefore likely to reduce the risk of infectious complications in TRbx. A clinical trial evaluating the quality of prostate specimens obtained by the Forsvall needle has been completed [15] and its ability to reduce infectious complications will be studied further in a prospective, randomized multicentre trial.…”
Section: Discussionmentioning
confidence: 99%
“…1 . The nodules determined by mpMRI scanning were biopsied through the rectum under ultrasound guidance by experienced urologists using the same method as described in previous studies [ 13 , 14 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%